Lithium-doped two-dimensional perovskite scintillator for wide-range radiation detection - Aozhen Xie (Nature Portfolio, 2020)
Two-dimensional lead halide perovskites have shown great potential as X- and γ-ray scintillators due to their high light yield, fast decay rate, and low fabrication cost. Here, their versatility is expanded by achieving, via Li-doping, α-particle/γ-ray discrimination and thermal neutron detection.